In situ synthesis of nitrogen- and sulfur-enriched hierarchical porous carbon for high-performance supercapacitor - Mehare, Rupali S.; Ranganath, Suresha P.; Chaturvedi, Vikash; Badiger, Manohar. V.; Shelke, Manjusha V. (Energy & Fuels, 2018)
In this work, we present a simple and facile method for the nitrogen (N)- and sulfur (S)- doped porous three-dimensional (3D) spongelike carbon materials via direct pyrolysis of N and S containing polymer N,N'-methylene-bis-acrylamide cross-linked poly(acrylamide-co-2-acrylamido-2-methyl-1-propanesulfonic acid) at varying temperatures under inert atmosphere. The obtained nitrogen- and sulfur-doped porous carbons (NSPCs) possess 3D hierarchical porous structure and contain a significantly high amount of N and S species. The concurrent incorporation of N and S successfully modified the surface properties of carbon materials and lead to enhanced capacitive performance. The presented NSPC exhibits specific capacitance of 230 F g(-1) at a current density of 1 A g(-1) and showed excellent cycling stability, depicting a promising material for energy storage devices.

Studies on the use of sodium polyacrylate (SPA) for low-salt animal skin preservation - Balasubramanian, Venkatakrishnan; Velappan, Brindha; Vijayan, Sandhya Kurvilla; Jabamani, Hepzibah; Nagarajan, Vedaraman; Victor, John Sundar; Ranganath, Suresha P.; Badiger, Manohar V.; Chinnaraj, Velappan kandukalpatti; Chellappa, Muralidharan (Environmental Science and Pollution Research, 2019)
Salt-based preservation is practiced for decades in the leather industry because of its versatility, cost-effectiveness, and availability. The salt removed from the soaking process causes significant pollution including organic and elevated total dissolved solids (TDS). Hence, a low-salt skin preservation method using commercial sodium polyacrylate with a reduced quantity of sodium chloride aiming to retain leather properties and pollution reduction was the principal focus of the study. Commercial sodium polyacrylate initially characterized for water absorption capacity along with structural and functional properties is confirmed by NMR and IR spectroscopic techniques. In preliminary experiments, the process parameters attained optimized conditions of sodium polyacrylate (SPA) quantity (5%), a minimal amount of salt (15%), and contact time (4 h) required for skin preservation. Besides, reusability studies after SPA recovery (95%) were applied to skins with an optimized quantity of SPA and salt subsequently stored for 15 days along with control (40% salt). The results revealed that SPA with low salt aided an adequate curing efficiency with a substantial reduction (> 65%) of TDS and comparable physical and organoleptic properties on par with the conventional method. Overall, SPA supported low-salt skin preservation reduces pollutant load (TDS) caused due to using of 40% sodium chloride in the conventional curing process.

F-doped nickel cobalt oxide-carbon composite electrocatalysts paired with mechanically robust anion-conducting chitosan membranes for flexible and rechargeable zinc-air batteries - Kurian, Maria; Ranganath, Suresha P.; Vijayakumar, Vidyanand; Sivadasan, Sneha; Kurian, Rachna Maria; Badiger, Manohar V.; Kurungot, Sreekumar (ACS Applied Energy Materials, 2024)
High-performing, cost-effective electrocatalysts and anion-conducting polymer electrolyte membranes are essential for realizing commercially affordable zinc-air batteries (ZABs). In this context, the present work deals with the development of a bifunctional electrocatalyst and an anion-exchange quasi-solid-state electrolyte membrane (based on quaternary ammonium group-grafted chitosan) for demonstrating flexible and rechargeable ZABs. The electrocatalyst composed of NiCoO2 nanoparticles supported on a carbon framework showcased substantial advancements in its ability to catalyze both oxygen reduction and evolution reactions (ORR and OER) due to the heteroatom doping by fluorine. For instance, the optimized electrocatalyst (F-NCO-ADC-600) exhibited an onset potential of 0.96 V vs RHE with a half-wave potential of 0.83 V vs RHE for ORR, a comparable performance with the state-of-the-art Pt/C (1.0 and 0.86 V vs RHE, respectively). On a similar note, the same catalyst also displayed an overpotential of 340 mV vs RHE for OER at a current density of 20 mA cm(-2), close to that of a standard RuO2 catalyst (337 mV vs RHE). In the context of polymer electrolytes, the quaternary ammonium-group-grafted chitosan membrane depicted superior ionic conductivity, liquid electrolyte uptake, and mechanical properties, thereby proving to be an efficient anion-conducting polymer electrolyte membrane. The realistic application of the developed electrocatalyst and the polymer electrolyte membrane is demonstrated in the ZAB prototypes. The assembled rechargeable ZAB (RZAB) delivered a power density of 207 mW cm(-2) and maintained high-rate capability and cycling stability, notably in a flexible configuration (f-RZABs). Thus, this work provides a strategy for the rational design of anion-exchange membranes and bifunctional electrocatalysts for f-RZABs.
Keywords: anion-conducting polymer electrolytemembrane; F-doping; flexible and rechargeable zinc-air batteries(f-RZABs); oxygen evolution reaction(OER); oxygen reduction reaction (ORR)

Insight Into the Influence of Salinity on Flow and Flocculation Behavior of Acrylamide-Based Cationic Polyelectrolyte - Ranganath, Suresha P.; Kurian, Rachna; Torris, Arun; Khairnar, Ajay; Ravindranathan, Sapna; Rajamohanan, P. R.; Badiger, Manohar V.; Wolf, Bernhard A. (Journal of Applied Polymer Science, 2026)
The viscometric behavior of aqueous solutions of acrylamide and acrylamidopropyl trimethylammonium chloride copolymers (AM-co-APTMAC) with varying cationic content under different salinity conditions was studied. Viscometric measurements were employed to determine intrinsic viscosity and quantify the influence of electrostatic interactions on chain conformation. Rheology experiments were performed to probe dynamic flow behavior under shear to obtain insights into polyelectrolyte viscoelastic properties under conditions mimicking industrial processes. Viscometric and rheology data analysis is augmented with insights from NMR relaxation and pulsed field gradient NMR diffusion experiments. Further, flocculation of kaolin suspensions was studied using aqueous solutions of AM-co-APTMAC copolymers with different charge fractions in the presence and absence of salt. The physicochemical insights on the behavior of AM-co-APTMAC polyelectrolytes in solution from this study could be relevant in practical applications, such as plants that use seawater or in cases where the ionic strength of suspensions is high due to salinity in the medium.
Keywords: copolymers; polyelectrolytes; structure property relationships; theory and modeling